KENDALI ROBOT BLUETOOTH DENGAN SMARTPHONE ANDROID BERBASIS ARDUINO UNO - Handayani, Yanolanda Suzantry; Mardiana, Yessi (ILKOM Jurnal Ilmiah, 2018)
The Mobile Robot is a robot construction whose characteristic is to have an actuator in the form of a wheel to move the entire body of the robot, so that the robot can shift positions from one point to another. This Mobile Robot is designed to move using an Android Smartphone controller that has an application that is suitable for robot movements. This robot uses Arduino Uno as a Bluetooth robot control system, the Bluetooth module functions as receiving commands sent via an Android Smartphone, a DC Motor is functioned as a controlled Robot drive using an Android Smartphone and Boarduino application installed via Playstore. The method used is the experimental method, the research will focus on communication between smartphone devices and Arduino Uno microcontrollers via Bluetooth to control robotic devices. Based on testing Bluetooth connections on robots, it can be concluded that the Bluetooth connection between the Smartphone and the Bluetooth robot can be fully controlled by a range of 25 meters, for a distance of 25-32 meters has a signal drop and is broken, and more than a range of 32 meters will experience a broken connection so that the robot cannot be controlled anymore.